Laboratório lúdico - Cardoso, Eduardo Mota (2016)
This work is theoretical and practical. His artistic practice is a laboratory (Flusser, 2008). It involves knowledge of creation and thought processes in the arts. It is inserted into the context of the nature and context of contemporary art and seeks to question the creative process in the arts. We operate with the possibilities that can frame practical sound and visual production through a playful action. Thus, we are not totally conditioned to viewers of the current reality, which would leave a way to possible work on the art of possibilities, where there is the intertwining of practices to produce a form of sound art that still incipient, let conflicts and open questions.